2003
DOI: 10.1152/ajpgi.00436.2002
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 downregulation of Smad1 gene expression in rat hepatic stellate cells

Abstract: Smads are intracellular signaling molecules of the transforming growth factor-β (TGF-β) superfamily that play an important role in the activation of hepatic stellate cells (HSCs) and hepatic fibrosis. Excepting the regulation of Smad7, receptor-regulated Smad gene expression is still unclear. We employed rat HSCs to investigate the expression and regulation of the Smad1 gene, which is a bone morphogenetic protein (BMP) receptor-regulated Smad. We found that the expression and phosphorylation of Smad1 are incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 36 publications
(28 reference statements)
2
43
0
Order By: Relevance
“…This assumption is supported by our findings that (i) ALK1 and ALK5 are expressed in HSCs and (ii) ALK1/Smad1 signaling but not ALK5/ Smad2/3 signaling induces Id1 expression in HSCs. Increased expression and phosphorylation of Smad1 during activation of HSCs has been reported previously, 32 pointing to a significant role of Smad1/5/8 signaling during transdifferentiation of HSCs. The existence of two TGF-␤/Smad pathways in HSCs, via ALK1 and ALK5, enables a careful fine-tuning of TGF-␤-induced biological responses.…”
Section: Discussionsupporting
confidence: 56%
“…This assumption is supported by our findings that (i) ALK1 and ALK5 are expressed in HSCs and (ii) ALK1/Smad1 signaling but not ALK5/ Smad2/3 signaling induces Id1 expression in HSCs. Increased expression and phosphorylation of Smad1 during activation of HSCs has been reported previously, 32 pointing to a significant role of Smad1/5/8 signaling during transdifferentiation of HSCs. The existence of two TGF-␤/Smad pathways in HSCs, via ALK1 and ALK5, enables a careful fine-tuning of TGF-␤-induced biological responses.…”
Section: Discussionsupporting
confidence: 56%
“…Liver fibrosis is the common response to chronic injury, a process with complex underlying integrated signaling networks and with various growth factors involved, of which the TGF-β signaling pathway is crucial, and also considered as the most potent stimulator to HSCs (22). Among the TGF-β subtypes, TGF-β1 is revealed to closely correlate with the progression of fibrosis, that is in accordance with our data, whereby increased expression of TGF-β1 was observed during the progression of hepatic fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…It is well established that BMPs elicit a Smad response in hepatocytes and stellate cells [59] but little is known about the response to BMPs of other liver cell types. In this respect, the only evidence of BMP activity in liver endothelial cells and in Kupffer cells comes from Miller et al, who demonstrated that BMP9 binds to both types of rat isolated liver cells.…”
Section: Bmp Signaling In the Livermentioning
confidence: 99%